Early postoperative complications following tracheotomy: Does suturing technique influence outcomes?. Issue 1 (1st December 2022) - Silva‐Nash, Jennifer; Campbell, Jessica B.; Gardner, James Reed; Daigle, Olivia; King, Deanne; Moreno, Mauricio; Vural, Emre; Tulunay‐Ugur, Ozlem E.
Abstract: Introduction: Tracheotomy is one of the most commonly performed procedure by otolaryngologists, but no consensus exists on the effect of suturing techniques on postoperative complications. Stay sutures and Bjork flaps are utilized frequently for securing the tracheal incision to the neck skin in order to create a tract for recannulation. Methods: Retrospective cohort study of tracheotomies performed by Otolaryngology‐Head and Neck Surgery providers (May 2014 to August 2020) was conducted to determine the effect of suturing technique on postoperative complications and patient outcomes. Patient demographics, medical comorbidities, indication for tracheostomy, and postoperative complications were analyzed with a statistical alpha set of .05. Results: Out of 1395 total tracheostomies performed at our institution during the study period, 518 met inclusion criteria for this study. Three hundred and seventeen tracheostomies were secured by utilizing a Bjork flap, while 201 were secured with up and down stay sutures. Neither technique was noted to be more commonly associated with tracheal bleeding, infection, mucus plugging, pneumothorax, or false passage of the tracheostomy tube. One mortality was noted following decannulation during the study period. Conclusion: Though various techniques exist; adverse outcomes are not associated with the manner in which a new tracheostomy stoma is secured. Medical comorbidities and the indications for tracheostomy likely play a more significant role in postoperative outcomes and complications. Level of evidence: Level 3. Abstract : Tracheotomy is one of the most common procedures performed by otolaryngologists and will substantially increase due to the COVID pandemic. There is continued debate on the effect of surgical stabilization techniques on complication rates. To our knowledge this is the first study solely assessing this question. Our cohort shows no difference between stay sutures and Bjork flap use.